Hi there!
When we have an equation standard form...
![a {x}^{2} + bx + c = 0](https://tex.z-dn.net/?f=a%20%7Bx%7D%5E%7B2%7D%20%2B%20bx%20%2B%20c%20%3D%200)
...the formula of the discriminant is
D = b^2 - 4ac
When
D > 0 we have two real solutions
D = 0 we have one real solutions
D < 0 we don't have real solutions
1.) Find the value of the discriminant and the the number of real solutions of
x^2-8x+7=0
Plug in the values from the equation into the formula of the discriminant
![( - 8) {}^{2} - 4 \times 1 \times 7 = 64 - 28 = 36](https://tex.z-dn.net/?f=%28%20-%208%29%20%7B%7D%5E%7B2%7D%20-%204%20%5Ctimes%201%20%5Ctimes%207%20%3D%2064%20-%2028%20%3D%2036)
D > 0 and therefore we have two real solutions.
2.) Find the value of the discriminant and the number of real solutions of
2x^2+4x+2=0
Again, plug in the values from the equation into the formula of the discriminant.
![{4}^{2} - 4 \times 2 \times 2 = 16 - 16 = 0](https://tex.z-dn.net/?f=%20%7B4%7D%5E%7B2%7D%20-%204%20%5Ctimes%202%20%5Ctimes%202%20%3D%2016%20-%2016%20%3D%200)
D = 0 and therefore we have one real solution.
~ Hope this helps you.
Answer:
b
Step-by-step explanation:
First, converting R percent to r a decimal
r = R/100 = 6.5%/100 = 0.065 per year,
then, solving our equation
I = 95000 × 0.065 × 20 = 123500
I = $ 123,500.00
The simple interest accumulated
on a principal of $ 95,000.00
at a rate of 6.5% per year
for 20 years is $ 123,500.00.
Considering that the value of 126.07 is valid for the population, it is a parameter.
<h3>What is the difference between a statistic and a parameter?</h3>
- If the measure is defined only for the sample, it is a statistic.
- If the measure can be defined for the population, it is a parameter.
In this problem, the mean blood pressure is calculated for all employees, which means that it is valid for the population, hence it is a parameter.
More can be learned about parameters and statistics at brainly.com/question/13794992
#SPJ1
In general point-point form, the equation for the line through (a,b) and (c,d) is
![(c-a)(y-b) = (d-b)(x-a)](https://tex.z-dn.net/?f=%28c-a%29%28y-b%29%20%3D%20%28d-b%29%28x-a%29)
Here we have (a,b)=(-1,7) and (c,d)=(-2,3)
![(-2 - -1) (y - 7) = (3 - 7)(x - -1)](https://tex.z-dn.net/?f=%28-2%20-%20-1%29%20%28y%20-%207%29%20%3D%20%283%20-%207%29%28x%20-%20-1%29)
![-1(y - 7) = -4(x+1)](https://tex.z-dn.net/?f=%20-1%28y%20-%207%29%20%3D%20-4%28x%2B1%29)
![y - 7 = 4 (x+1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%204%20%28x%2B1%29)
Answer: Choice D